The remote-oxyfunctionalization of unactivated carbons in (5β)-3-oxobile acids by 2,6-dichloropyridine N-oxide catalyzed by ruthenium–porphyrin and HBr: a direct lactonization at C-20 - Ogawa, Shoujiro; Iida, Takashi; Goto, Takaaki; Mano, Nariyasu; Goto, Junichi; Nambara, Toshio (Organic & biomolecular chemistry, 2004)
Remote-oxyfunctionalization induced by 2,6-dichloropyridine N-oxide (DCP N-oxide) as an oxygen donor and a (5,10,15,20-tetramesitylporphyrinate) ruthenium(II) carbonyl complex (Ru-porphyrin) and HBr as catalysts was examined for a series of methyl ester-peracetylated derivatives of (5beta)-3-oxobile acids. Using the DCP-N-oxide/Ru-porphyrin/HBr system, 5beta-hydroxylation predominated for the substrates having a 12-acetoxyl substituent due to steric hindrance, but the presence of a 7-acetoxyl substituent decreased the reactivity of the 5beta-position allowing for the competitive (20S)-20-oxyfunctionalization, subject to electronic constraints. A variety of novel 5beta-hydroxylation and (20S)-24,20-gamma-lactonization products, as well as their double-oxyfunctionalization and dehydration products, were obtained in one-step. The alkaline hydrolysis of the gamma-lactones gave the corresponding stereoselective (20S)-20-hydroxy- carboxylic acids.